Original paperThe subjective assessment of the effect and satisfaction with dermocosmetics use by patients with skin disturbances - Olszanecka-Glinianowicz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Atopic dermatitis and different constellations and the severity of symptoms that not meet the criteria for this diagnosis are a common skin disturbances. An important component of the treatment of these diseases and the proper care of sensitive and dry skin is local dermocosmetics use. Aim: To assess the frequency of skin disturbances and the effect and satisfaction with Atoperal products use as well as the source of information about these products. Material and methods : A questionnaire survey about the type of skin disturbances, the subjective assessment of the effect and satisfaction with Atoperal products use and source of information about these products was performed by 787 general practitioners, internists, pediatricians, dermatologists, allergists and pulmonologists and 252 pharmacists in a group of 51 085 subjects with skin disturbances. Results: In the group interviewed by doctors, the most common skin problem was atopic dermatitis (52.5%) and in the group interviewed by pharmacists, pruritus (70.0%). In both groups, respondents after Atoperal products use most frequently reported improving of the skin hydration and greasiness of the skin and reduction of itching. In both groups, over 90.0% of respondents were satisfied or very satisfied with Atoperal products use. In the group surveyed by doctors, 75.5% of respondents obtained information about these products from doctors and 17.4% from pharmacists, while in the group surveyed by pharmacists, 48.9% from pharmacists and 36.1% from doctors. Conclusions : Atopic dermatitis was most frequently diagnosed in a group surveyed by doctors. The main skin disturbance that occurred in a group surveyed by pharmacists was skin pruritus. The main effect of Atoperal products use, independent of the place of the survey, included improving of skin hydration and greasiness of the skin and reduction of itching. In a study population, there was a high level of satisfaction from the use of Atoperal products. Doctors and pharmacists were the main sources of information about Atoperal products depending on the place of the survey.